Letter - Outram, Harold
021-0101-001 24 Feb 1937 OFFICIAL AND EXCLUSIVE EUROPEAN NEWS PICTURE GATHERING ORGANIZATION FOR THE ASSOCIATED PRESS (OF AMERICA) The Associated Press of Great Britain. Ltd. NEWS PHOTO DEPARTMENT. 20, TUDOR STREET, LONDON, E.C.4. DIRECTORS KENT COOPER U.S.A Chairman LLOYD STRATTON " President GIDEON D. SEYMOUR, " Managing Director FRANK H. KING " Secretary TELEPHONES: CENTRAL 1515 (7 LINES) TELEGRAMS (Inland) APPHO. TELEX. LONDON. CABLES & FOREIGN TELEGRAMS: APPHO, LONDON. MAIN BRANCHES NEW YORK 383 MADISON AVENUE BERLIN MARKGRAFENSTRASSE 77 PARIS 21 RUE VIVIENNE VIENNA, 1 TRATTNERHOF 2 J.J. WURZEL, DIRECTING NEWS PHOTO EDITOR FOR EUROPE February 23, 1937 Sir Walter Citrine, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Sir, We should be glad if you would kindly let us have any permits necessary for taking photographs for the Press during the International conference in London on March 10 and 11. We are interested in all the meetings or other functions. Thanking you in anticipation, Yours faithfully, Harold Outram News Photo Editor fnb 292/946/21/101